2010
DOI: 10.1111/j.1365-2125.2010.03760.x
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate infliximab infusion dosage and monitoring: results of a panel meeting of rheumatologists, dermatologists and gastroenterologists

Abstract: Infliximab is an effective treatment for rheumatoid arthritis, ankylosing spondylitis, Crohn's disease (both adult and paediatric), ulcerative colitis, psoriatic arthritis and plaque psoriasis and national and international guidelines have been developed for each indication. WHAT THIS STUDY ADDSThis study is the first study which compared current international, national and local guidelines from the medical specialties involved in the treatment with infliximab on the following topics: indication, dosage, syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
0
20
0
3
Order By: Relevance
“…However, concomitant immunosuppression (e.g. azathioprine, methotrexate) is generally recommended in IBD but not in psoriasis (38).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…However, concomitant immunosuppression (e.g. azathioprine, methotrexate) is generally recommended in IBD but not in psoriasis (38).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Vital parameters such as blood pressure, pulse frequency and body temperature are usually assessed and documented during infliximab infusions, but to date no study has shown that the routine measurement of vital signs can better predict, help to recognize or handle infusion reactions to infliximab. An expert panel of rheumatologists, dermatologists and gastroenterologists has recommended measuring vital signs at baseline to rule out possible infections or other contraindications before the administration of infliximab, and to only provide the therapy in centers and units trained to handle infusion reactions [92].…”
Section: Gastrointestinal Toxicitymentioning
confidence: 99%
“…[11]. Основным преимуще-ством биологической терапии является максимальная избирательность воздействия на иммунную систему, позволяющая устранить необходимое звено в патогене-тической цепи, не воздействуя на клетки других органов и систем [12].…”
Section: обоснованиеunclassified
“…[11]. Основным преимуще-ством биологической терапии является максимальная избирательность воздействия на иммунную систему, позволяющая устранить необходимое звено в патогене-тической цепи, не воздействуя на клетки других органов и систем [12].Центральное звено в патогенезе ЮИА без систем-ных проявлений -фактор некроза опухоли (ФНО) ␣. Он обладает цитотоксическими, иммуномодулирующими и провоспалительными свойствами, обусловливая хро-ническое воспаление, деструкцию хряща и кости, потерю костной массы [13].…”
unclassified